Self-regulated learning in students of pedagogy - Marini, Janete Aparecida da Silva; Boruchovitch, Evely (Paidéia (Ribeirão Preto), 2014)
Self-regulated learning is the process by which students plan, monitor and regulate their own learning. The aim of this study was to investigate relationships between motivation to learn, implicit theories of intelligence and self-handicapping strategies, and to examine the association of these variables in the prediction of the use of learning strategies in students of Pedagogy. The sample consisted of 107 Pedagogy students of two private universities of a city of São Paulo state. Data were collected using four Likert-type scales. Multivariate linear regression analyses revealed that participants with higher scores in the Learning Strategies Scale also presented significantly higher scores in intrinsic motivation and fewer reports of use of self-handicapping strategies. Higher scores in metacognitive strategies were significantly associated with both intrinsic an extrinsic motivation and with fewer reports of use of self-handicapping strategies. Results are discussed in terms of the contribution of Psychology to teacher education.